2009
DOI: 10.1111/j.1469-8137.2009.02833.x
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic nucleotide‐gated channel is necessary for optimum fertility in high‐calcium environments

Abstract: Summary Arabidopsis cngc2 plants are hypersensitive to external calcium and exhibit reduced plant size and fertility, especially when they are treated with elevated but physiologically relevant levels of calcium. This report focuses on the role of cyclic nucleotide‐gated channel 2 (CNGC2) in plant fertility. To determine the cause of the reduced fertility, we investigated the flower structure and growth potential of both male and female reproductive organs in cngc2 plants grown in high‐calcium conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…This level of lethality is 2-to 3-fold higher than a wild-type control. An analogous CaCl 2 hypersensitivity has been reported for two other cngc mutant phenotypes (Chaiwongsar et al, 2009;Urquhart et al, 2011). For example, the growth reduction phenotype associated with a knockout of cngc2 in Arabidopsis was further decreased by approximately 2-fold by supplementing soil with 10 mM CaCl 2 .…”
Section: Germination Of Cngc16 Pollen Grains Is Highly Sensitive To Ementioning
confidence: 84%
“…This level of lethality is 2-to 3-fold higher than a wild-type control. An analogous CaCl 2 hypersensitivity has been reported for two other cngc mutant phenotypes (Chaiwongsar et al, 2009;Urquhart et al, 2011). For example, the growth reduction phenotype associated with a knockout of cngc2 in Arabidopsis was further decreased by approximately 2-fold by supplementing soil with 10 mM CaCl 2 .…”
Section: Germination Of Cngc16 Pollen Grains Is Highly Sensitive To Ementioning
confidence: 84%
“…Many studies have explored the role of CNGC2 (CYCLIC NUCLEOTIDE GATED CHANNEL2) in regulation of Ca 2+ fluxes across the plasma membrane and its contribution to signaling in the context of immunity [53,54], senescence [55], heat stress [56], and pollen growth [57]. Null mutation of CNGC2 was first isolated as defense no death1 ( dnd1 ), a mutant which exhibits a lesion mimic phenotype which is dependent on growth conditions [58], increased accumulation of SA and constitutive defense activation [59], and altered Ca 2+ transport [60].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gene expression profiling of cngc2-2 showed strong similarity to the expression pattern of wild-type plants grown at elevated Ca 2+ levels, indicating abnormal Ca 2+ sensing in cngc2 (Chan et al , 2008). Adult cngc2 mutants displayed decreased size and fertility when grown on Ca 2+ -supplemented medium (Chan et al , 2003; Chaiwongsar et al , 2009). Pollen tube growth is another developmental process that is driven by Ca 2+ fluxes (Michard et al , 2009), and it has been shown that the loss of AtCNGC18 causes abnormalities in pollen tube growth (Frietsch et al , 2007; Chang et al , 2008).…”
Section: Introductionmentioning
confidence: 99%